2016
DOI: 10.1111/ppa.12628
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia solanacearum virulence in tomato seedlings inoculated by leaf clipping

Abstract: Ralstonia solanacearum is a phytopathogenic bacterium that colonizes the xylem vessels of host plants leading to a lethal wilt disease. Although several studies have investigated the virulence of R. solanacearum on adult host plants, infection studies of this pathogen on the seedling stages of hosts are less common. In a preliminary observation, inoculation of R. solanacearum F1C1 on 6-to 7-day-old tomato seedlings by a simple leaf-clip strategy resulted in a lethal pathogenic condition in seedlings that event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
3
32
1
Order By: Relevance
“…Colonization of F1C1 in the inoculated eggplant seedlings was demonstrated by the GUS staining of the infected seedlings as performed previously in tomato seedlings (Kumar et al 2017). GUS staining was observed along the shoot region of the seedlings suggesting that growth and migration of the bacteria occurred towards the root region from the inoculated site in the cotyledon leaves along with the shoot (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Colonization of F1C1 in the inoculated eggplant seedlings was demonstrated by the GUS staining of the infected seedlings as performed previously in tomato seedlings (Kumar et al 2017). GUS staining was observed along the shoot region of the seedlings suggesting that growth and migration of the bacteria occurred towards the root region from the inoculated site in the cotyledon leaves along with the shoot (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…The other possible reason may be that the pathogenicity assays used till date are more consistent and reproducible in tomato than in eggplant. In this present study we have demonstrated that the leaf-clip inoculation method is an easy and stable method for evaluating the virulence of R. solancearum in eggplant seedlings, which was ever successfully used to test R. solanacearum virulence in tomato seedlings (Kumar et al 2017). This is an easy and stable method of inoculation in which the juvenile seedlings are maintained in 1.5 or 2.0 mL microfuge tubes.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Bacterial inoculums were used for infection by root inoculation approach in 6-7 days old tomato seedlings as stated above. After third day of post inoculation, tomato seedlings were employed for colonization study and infected seedlings were surface sterilized by the method of Kumar et al ., (2016) (Kumar et al , 2017). After surface sterilization, seedlings were observed under the fluorescence microscopy (EVOS FL, Life technologies) for bacterial colonization study in 40X magnification adjusted in RFP filter.…”
Section: Methodsmentioning
confidence: 99%
“…To demonstrate the functionality of GG-assembled expression modules, we first focused on the construction of an expression cassette containing the uidA gene. The uidA reporter gene was chosen as an Rssc strain expressing this reporter is easily traceable in infected tomato plants (Kumar et al, 2016). The expression construct was generated by fusing an eps promoter (LI A-B), the uidA CDS (LI C-D), the GFP CDS (LI D-E), a Tfd terminator (LI E-F) and a tetracycline resistance gene (LI F-G) via BsaI cut-ligation into an LII destination vector (Fig.…”
Section: Gg-based Assembly Of a Uida-gfp Expression Cassette For Use mentioning
confidence: 99%